Advantages of Proactive Therapeutic Drug Monitoring in a Prospective Cohort of Children With Inflammatory Bowel Disease Treated With Anti-Tumour Necrosis Factor. Issue 4 (3rd April 2022) - Gasparetto, Marco; Burgess, Natasha; Naik, Sandhia; Studart, Dominic; Kadir, Ahmed; Croft, Nick; Sanderson, Ian; Deb, Protima
Abstract : ABSTRACT: Few studies have addressed whether proactive therapeutic drug monitoring (TDM) results in improved clinical outcomes in children with inflammatory bowel disease (IBD) treated with anti-tumour necrosis factor. The aim of this study was to investigate the impact of using proactive TDM in this patient group. Pilot single-centre observational study to accrue data on patients managed with proactive TDM. More patients in the proactive TDM cohort were managed by escalating the infliximab (IFX) regime ( P  < 0.001). The need for switching to different biologics was significantly lower in this patient group ( P  < 0.001). The introduction of proactive TDM resulted in a significant reduction of patients requiring switch of their primary biologic. The results of this study are indicators that proactive TDM offers a better method of managing children with IBD on IFX therapy.